Bictegravir/Emtricitabine/Tenofovir Alafenamide Treatment: Efficacy and Tolerability in Clinical Practice - Canetti D; Galli L; Lolatto R; Nozza S; Spagnuolo V; Muccini C; Trentacapilli B; Bruzzesi E; Ranzenigo M; Chiurlo M; Castagna A; Gianotti N (Dove Medical Press, 2023)
Diana Canetti,1 Laura Galli,1 Riccardo Lolatto,1 Silvia Nozza,2 Vincenzo Spagnuolo,1 Camilla Muccini,1 Benedetta Trentacapilli,2 Elena Bruzzesi,2 Martina Ranzenigo,2 Matteo Chiurlo,2 Antonella Castagna,1,2 Nicola Gianotti1 1Infectious Diseases Unit, San Raffaele Scientific Institute, Milan, Italy; 2Infectious Diseases Unit, Vita Salute San Raffaele University, Milan, ItalyCorrespondence: Diana Canetti, Infectious Diseases Unit San Raffaele Scientific Institute, Via Stamira D'Ancona 20, Milano, 20127, Italy, Tel +390226432461, Fax +390226437943, Email canetti.diana@hsr.itObjective: Analysis of bictegravir/emtricitabine/tenofovir alafenamide (BFTAF) efficacy and safety in virologically suppressed people living with HIV (PLWH) in clinical practice.Patients and methods: The retrospective cohort study, which included adult treatment-experienced and virologically suppressed PLWH, switched to BFTAF from June 2019 to June 2021. Efficacy and safety were evaluated as virological failure (VF=2 consecutive HIV-RNA> 50 copies/mL or a single HIV-RNA> 400 copies/mL) and treatment failure (TF=VF or discontinuation for any reason) until data freezing (August 2022).Results: Of the 1040 PLWH included, 67.8% switched from elvitegravir/cobicistat/FTAF. VF occurred in 4.2% (n=44), with incidence rate of 1.63 per 1000 person-months of follow-up (PMFU) and probability at 24- 30 months of 3.8%- 4.0%, respectively. Out of the 44 VF, in 75% virological re-suppression was achieved while maintaining BFTAF. Discontinuation occurred in 15% after a median time of 13.5 months of follow-up, with an incidence rate of 5.67 per 1000 PMFU, and a probability at 24- 30 months of 11.9%- 15.3%, respectively. Main discontinuation reasons were simplification (51.3%) and toxicity (21.8%, involving CNS in half of cases). TF occurred in 18.6% with an incidence rate of 7.01 per 1000 PMFU after a median time of 13.6 observation months; probability at 24- 30 months was 14.8%- 18.4%, respectively.Conclusion: BFTAF has proven effective and well tolerated in clinical practice.Plain Language Summary: In Clinical Randomized Trials, BFTAF proved to have a high genetic barrier regimen.In this context of clinical practice:BFTAF proved effective and well toleratedIt showed a low rate of virological failureDiscontinuation was largely influenced by simplification with 2-drug regimens.Keywords: bictegravir, people living with HIV, PLWH, efficacy, safety, clinical practice